Overview on the cellulose based conducting composites - Pandey, Jitendra Kumar; Takagi, Hitoshi; Nakagaito, Antonio Norio; Saini, Daulat Ram; Ahn, Sung-Hoon (Composites Part B-Engineering, 2012)
Biopolymer based composites have been employed in numerous applications with increasing interest not only due to renewable, eco-friendly nature, but also because of the flexibility in processing conditions and competitive cost of their end products. The conductive materials from biopolymers have been found applicable in robots, medical imaging, sensitive membranes, actuators, visual displays, electronic wiring and shielding, and components in batteries. Cellulose is one of the most abundant biopolymers in the nature, which has received special attention for development of conducting materials due to biocompatibility for protein and drug immobilization and ability to form the composites with synthetic polymers. The present review is aimed to provide concisely the current status in this field of conducting composites from cellulose, with brief discussions of associated problems and future applications. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Fibres; mechanical properties; Nano-structures; Polymer-matrix composites (PMCs)